2005
DOI: 10.1002/nme.1466
|View full text |Cite
|
Sign up to set email alerts
|

On 2D elliptic discontinuous Galerkin methods

Abstract: SUMMARYWe discuss the discretization using discontinuous Galerkin (DG) formulation of an elliptic Poisson problem. Two commonly used DG schemes are investigated: the original average flux proposed by Bassi and Rebay (J. Comput. Phys. 1997 1119 -1148) by adopting a matrix based notation with a view to highlighting the steps required in a numerical implementation of the DG method. Through consideration of standard C 0 -type expansion bases, as opposed to elementally orthogonal expansions, with the matrix formula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
37
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 24 publications
2
37
0
Order By: Relevance
“…In [29] a block diagonal preconditioner for linear problems based upon a domain decomposition method with static condensation is seen to achieve an optimal convergence where the convergence rate of the implicit iterative solver is independent of the number of DOF. Static condensation was also successfully applied to a direct solver in [42]. Multigrid approaches where convergence acceleration is achieved through the use of coarse levels constructed by reducing the polynomial degree (p-multigrid) or using coarser grids with fewer elements (h-multigrid) have also been proposed [18,25,36].…”
mentioning
confidence: 99%
“…In [29] a block diagonal preconditioner for linear problems based upon a domain decomposition method with static condensation is seen to achieve an optimal convergence where the convergence rate of the implicit iterative solver is independent of the number of DOF. Static condensation was also successfully applied to a direct solver in [42]. Multigrid approaches where convergence acceleration is achieved through the use of coarse levels constructed by reducing the polynomial degree (p-multigrid) or using coarser grids with fewer elements (h-multigrid) have also been proposed [18,25,36].…”
mentioning
confidence: 99%
“…All the methods considered in the unifying analysis of DG methods for second-order elliptic problems in [1], which use polynomial approximations of degree k for both the potential and the flux, converge with the optimal order of k + 1 for the potential and with the suboptimal order of k for the flux. Since the classic continuous Galerkin method needs considerably less degrees of freedom, on the same mesh, and converges with exactly the same orders, the use of DG methods for second-order elliptic equations has been judged as not being particularly advantageous; see, for example, [15]. In [9], the HDG methods were introduced to address this criticism.…”
mentioning
confidence: 99%
“…In both cases however the formulation is not adjoint consistent and one may not prove L 2 -convergence using the Nitsche trick. The question of how much the discontinuous Galerkin method needs to be stabilized was discussed in the case of mixed formulations of elliptic problems by Sherwin et al in [20] and by Marazzina in [16]. It was found that stabilization needs to be applied on the boundary of the domain only to assure well-posedness of the discrete system.…”
mentioning
confidence: 99%